Nimbus Series - Berndnaut Smilde (Oz, 2016)
The Nimbus works present a transitory moment of presence in a specific location. They can be interpreted as a sign of loss or becoming, or simply as a fragment from a classical painting. People have always had a strong, metaphysical connection to clouds and through time have projected many ideas on them.